(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Background: Myopia significantly decreases the frequency and severity of diabetic retinopathy (DR). The proliferative form of this diabetic complication in the retina is known to be very uncommon in diabetic myopes. The mechanisms of this phenomena are, however, still unclear. Studies on these mechanisms and the clarification of the structural changes in retinal neurons in animal models of both diabetes and myopia are critical to the research of the pathogenesis and further identification of therapeutic and preventive targets for these pathological conditions. Purpose: To examine changes in the retinal brain-derived neurotrophic factor (BDNF) concentration and the relationship of the latter with the structure of retinal neuronal cells in rats with induced both diabetes and axial myopia. Material and Methods: Rats (age, 2 to 10 weeks) were assigned to four groups: group 1 (myopia only, n = 15), group 2 (diabetes only, n = 15), group 3 (myopia plus diabetes, n = 15), and group 4 (healthy controls, n = 10). Axial myopia was produced in two-month-old animals by surgically fusing the eyelids of both eyes. Streptozotocin (STZ) (15 mg/kg body weight, intraperitoneally consequently for 5 days) was used to induce diabetes. Diabetes was induced in group 3 at 3 weeks after the initiation of the experiment. At 2 months, all rats were euthanized under anesthesia, and their eyes were enucleated. To perform a histomorphological study, serial retinal sections were made and stained with hematoxylin and eosin, and microscopy was performed and images were collected and evaluated on a light microscope Jenamed 2. Rat BDNF enzyme-linked immunosorbent kits (Elabscience, Houston, TX) were used to determine BDNF concentrations in retinal supernatant and plasma. Results: Rats with both diabetes and myopia exhibited smaller reductions in plasma and, especially, retinal BDNF concentrations compared to rats with diabetes only. Retinal BDNF concentrations in rats with both diabetes and myopia were 36.1% higher than in rats with diabetes only. Unlike rats with STZ-induced diabetes only, those with STZ-induced diabetes in the presence of experimental myopia exhibited a rather high neuronal cell density in the retinal ganglion cell layer. No noticeable change in the cell density in the inner nuclear layer and photoreceptor layer was observed in the latter animals. Conclusion: Axial length elongation secondary to experimental myopia in animals facilitates the protection against diabetic changes in the retina, which was confirmed at the molecular and morphological levels, with BDNF being a possible component of this protective mechanism.